Green Thumb, Rich Harvest: Exploring Bioactive Compounds in Horticulture - , T. Senthilkumar; , S. Jaya Prabhavathi; , G. Gomadhi; , A. Krishnaveni; , A. Punitha; , S.Anandha Krishnaveni; , D. Vidhya; , G. Malathi (Archives of Current Research International, 2024)
Horticulture, beyond its aesthetic allure, unveils a world rich in bioactive compounds with profound implications for human health and environmental sustainability. This abstract explores the diverse array of bioactive compounds found in horticultural crops and their potential benefits. Phytochemicals, such as phenolics, flavonoids, alkaloids, and terpenoids, are key players, contributing to plant defense mechanisms and human health. Polyphenols, including flavonoids, exhibit antioxidant properties, reducing the risk of chronic diseases. Glucosinolates in cruciferous vegetables showcase anticancer potential, while essential oils in aromatic herbs offer antimicrobial benefits. Importantly, the cultivation and consumption of bioactiverich horticultural crops promote sustainable agriculture by reducing chemical inputs and enhancing biodiversity. By harnessing the therapeutic potential of nature's pharmacy, horticulture emerges as a pivotal force in fostering human wellbeing and environmental resilience.